Larger Sensitivity of Precipitation Extremes to Aerosol Than Greenhouse Gas Forcing in CMIP5 Models. Issue 15 (15th August 2018) - Lin, Lei; Wang, Zhili; Xu, Yangyang; Fu, Qiang; Dong, Wenjie
Abstract: The sensitivity of precipitation extremes (PEs; i.e., the change in PE per degree of change in global mean surface temperature) to aerosol and greenhouse gas (GHG) forcings is examined using the twentieth century historical multimodel ensemble simulations from the Coupled Model Intercomparison Program phase 5 (CMIP5). We find a robustly larger sensitivity of PE to aerosols than GHGs across all available models. The aerosol/GHG‐induced sensitivity ratios for globe‐averaged monthly maximum consecutive 5‐day precipitation (RX5day) and maximum 1‐day precipitation (RX1day) in the multimodel ensemble are 1.6 and 1.4, respectively. Over land, the corresponding ratios for RX5day and RX1day are 2.3 and 1.8, respectively. In particular, the aerosol forcing leads to several times greater sensitivity than GHG forcing in West Africa, eastern China, South and Southeast Asia, northwestern South America, and Eastern Europe. The atmospheric energy balance, dynamical adjustment, and vertical structure of forcing, all contribute to the difference in the PE sensitivity to the two forcings. It is shown that the fast response primarily contributes to the greater‐than‐one aerosol‐to‐GHG ratios of the PE sensitivities, as for the mean precipitation. This is because of a stronger rainfall suppression effect induced by the GHG atmospheric forcing. We also find that the aerosol‐to‐GHG ratios of the PE sensitivities depend on the defined extreme precipitation indices. The aerosol‐to‐GHG sensitivity ratio is larger for more loosely defined PE, and it gradually converges to one for more severely defined PE. Our results further highlight the importance of considering the anthropogenic aerosol reduction in projecting the change in PE. Plain Language Summary: Precipitation extreme (PE) has wide‐ranging societal impacts. Warming caused by greenhouse gas (GHG) increases primarily contributes to the increase in PE during recent decades. To mitigate the air pollution, the expected declines of anthropogenic aerosols in the 21st century would impose an additional warming on the Earth, which will aggravate the PE caused by GHGs‐induced warming. The ultimate response of PE is thus related to the strength of various forcing agents, and the sensitivity of PE to various forcing agents. We show whether the difference in the PE sensitivity between GHGs and aerosols is robust across models and what mechanisms lead to the difference. A robustly larger sensitivity of PE to aerosols than GHGs across all available models is found. This sensitivity difference is primarily associated with the fast response of PE to various forcings. This study further highlights the importance of considering the anthropogenic aerosol reduction in projecting the change in PE. It has implications for policy making on climate adaptation to PE. Key Points: CMIP5 multimodel ensemble simulations robustly show a larger sensitivity of precipitation extremes to aerosol than GHG forcing This sensitivity difference is primarily associated with the fast response of precipitation extremes to various forcings This sensitivity difference depends on the definitions of precipitation extremes